Analyzing the Determinants of Export Trade in Cameroon (1970 – 2008) - Ngouhouo, Ibrahim; Makolle, Alex Audrin (Richtmann Publishing, 2013)
This research analyses empirically the determinants of export trade in Cameroon from 1970 to 2008. We use the two StageLeast Square to show that exchange rate, trade openness and export lag one period are the main determinants of export inCameroon. This result, although common in most Developing Countries are in contradiction with former studies, mostlybecause the foreign direct Investment was found to be not significant in determining the export in this Country.